DEVELOPMENT OF PROJECT-BASED LEARNING TEACHING MATERIALS OF THE RESEARCH RESULTS STUDY COURSE TO IMPROVE STUDENTS' ABILITIES IN COMPILING SCIENTIFIC WORKS - Suyatno Sutoyo (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research is aimed at developing project-based learning teaching materials in research results study courses to improve students' abilities in compiling scientific work. This research is developmental research using a modified Research and Development (R & D) model. This research is limited to the preliminary study stage, which includes literature study, field survey, initial product preparation followed by validation of product by experts (expert judgment) and product revision. The teaching materials developed consist of the lesson plan, student activity sheets, and assessment of project product. The research data were analyzed descriptively quantitatively. The research results showed that the teaching materials developed, namely the lesson plan, student activity sheets, and assessment of project product were categorized as very valid, with an average validity score of 3.80, 3.81 and 3.66, respectively. Thus, these teaching materials can be implemented in learning research results study courses to improve students' abilities in compiling scientific work.